The Relationship Between Financial Leverage and Firm Value in Emerging Markets - Dessy Evianti; Leonard Pangaribuan; Suratminingsih Suratminingsih; Lisdawati Lisdawati; Muhammad Yusuf (CV. Astina Mandiri, 2024)
This study examines the relationship between financial leverage and firm value in emerging markets, focusing on how leverage influences value creation in dynamic economic environments. Financial leverage, often utilized to enhance returns through debt financing, is a pivotal strategy for firms aiming to optimize capital structures. However, in emerging markets, where economic conditions, regulatory frameworks, and capital market developments vary significantly, the impact of financial leverage on firm value remains a subject of debate. Employing panel data analysis, this research evaluates a sample of firms from multiple emerging economies, considering factors such as profitability, growth opportunities, and macroeconomic indicators. The findings reveal a nonlinear relationship, suggesting that moderate levels of leverage contribute positively to firm value by lowering the cost of capital and signaling growth potential. Conversely, excessive leverage leads to financial distress risks, diminishing firm value. These results underscore the importance of maintaining an optimal leverage level to balance growth aspirations with financial stability. The study also highlights that institutional quality and market maturity significantly moderate this relationship, emphasizing the need for tailored financial strategies in emerging markets. By offering empirical insights, this research contributes to the ongoing discourse on corporate finance strategies in diverse economic settings, providing valuable implications for managers, investors, and policymakers seeking to enhance firm value in evolving market conditions.